2021
DOI: 10.3390/ijms22063192
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Host Protection against Helicobacter pylori Infections

Abstract: This narrative review discusses the genetics of protection against Helicobacter pylori (Hp) infection. After a brief overview of the importance of studying infectious disease genes, we provide a detailed account of the properties of Hp, with a view to those relevant for our topic. Hp displays a very high level of genetic diversity, detectable even between single colonies from the same patient. The high genetic diversity of Hp can be evaded by stratifying patients according to the infecting Hp strain. This appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…To establish the chronic infection of the host, bacteria should modulate the immune system of the host, which could enhance resistance and virulence in response to each other between hosts and pathogens [ 39 ]. H. pylori could have a system to control the host immune response and protect the host against autoimmune diseases, asthma, and esophageal adenocarcinoma, which could also be considered a potential factor of cell cellular damage in the result of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To establish the chronic infection of the host, bacteria should modulate the immune system of the host, which could enhance resistance and virulence in response to each other between hosts and pathogens [ 39 ]. H. pylori could have a system to control the host immune response and protect the host against autoimmune diseases, asthma, and esophageal adenocarcinoma, which could also be considered a potential factor of cell cellular damage in the result of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the accumulation of mtDNA mutations in H. pylori patients could be related to the modulated immune system by the bacterial pathogen [ 39 ], which also be considered a crucial factor for mtDNA integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, authors have indicated that H. pylori infection affects oxidative stress status of the host [ 56 , 57 , 58 ]. However, the consumption of dietary antioxidants can be effective to reduce negative aspects of H. pylori [ 59 ].…”
Section: Healthy Effects Of Polyphenols and Antioxidantsmentioning
confidence: 99%
“…The Red Queen dynamics force the host and pathogen to constantly adapt, evolve, and replicate in order to survive; briefly, to continuously evolve [9]. The Red Queen dynamics explains how the successful pathogens are those that more efficiently contrast host defense genes; at the same time, it reminds us that the success of the pathogen or of the host is ephemeral [10,11]. Yet, this input (that the success of the pathogen or the host is short-lived) is disregarded from genetic studies dealing with host protection against pathogens.…”
Section: Bacterial Infectionsmentioning
confidence: 99%